Comparison of Crystal Structure Between Carbonated Hydroxyapatite and Natural Bone Apatite with Theoretical Calculation - Yang, W.H.; Xi, X.F.; Li, J.F.; Cai, K.Y. (Asian Journal of Chemistry, 2013)
In this study, nanosized carbonated hydroxyapatite and stoichiometric hydroxyapatite were synthesized. Chemical analyses, as well as infrared spectroscopy and X-ray diffraction, were applied to investigate the composition, structure and chemical groups of all the samples. Furthermore, the structure and the crystal energy of all samples were analyzed by software and the mathematic methods. The results show that when CO32- is added into the solution after the reaction, the carbonated hydroxyapatite samples and natural bone apatite are similar in crystal structure, composition and crystallite size. Chemical analyses suggest that natural bone apatite and all synthetic carbonated hydroxyapatite samples have the same molecular formula. Meanwhile, the computed crystal energy indicates that the carbonated hydroxyapatite type-B substitution has lower crystal energy and better stability. Moreover, the fitting FTIR spectra prove that there is more type-B substitution than type-A substitution in all samples.